EFFECT OF ENERGY DRINK ON MICROHARDNESS OF DENTAL ENAMEL (IN VITRO) - Prima Ulva; Idral Purnakarya; Arymbi Pudjiastuty (Andalas Dental Journal, 2018)
A prolonged acidic ambience of oral environment will lead to demineralization process. It caused erosion to enamel surface after long time of exposure. Acidic beverages become the external factor of dental erosion. Energy drink is one of popular beverages which has acid ingredients and pH value below the critical pH (5.5). The objective is to determine the effect of energy drink on microhardness of dental enamel (in vitro). Methods that were used in this study was experimental pre test - post test with control group design. A total of 36 premolar were used as samples which were divided into energy drink group and control group of artificial saliva. The treatment group were immersed for 8 cycle for 7 days. Dental enamel microhardness were measured by Vickers Hardness Tester before and after treatment. The result of this study was microhardness mean of enamel surface decreased from 306 VHN to 262 VHN after immersion for energy drink group and no significant difference in artificial saliva group. Independent T-test analysis showed p value <0,005, thus concluding there was significant difference between two groups. The conclusion of this study there was significant effect of energy drink immersion to dental enamel microhardness.